Hukum dan Keadilan dalam Perspektif Filsafat Hukum - Putrado, Nodi (AHKAM, 2022)
Justice in the perspective of legal philosophy towards society. Law has close relevance to justice. There are even people who hold the view that the law must be combined with justice, in order to truly mean it as a law. This is related to the response that the law is part of the human effort to create an ethical co-existence in the world. The method used is descriptive is a research method that seeks to describe and interpret objects according to what they are. This study is also often called nonexperiment, because in this study the study did not control and manipulate the research variables. In law enforcement and justice, these things should be a guide for the apparatus involved in law enforcement, especially judges as the spearhead of distributing justice to the community. First, dare to find a new path (rule breaking) and not allow yourself to be constrained by the old and traditional way of living the law, which obviously hurts the sense of justice more. Second, it is living the old and traditional law, which obviously hurts the sense of justice more. Secondly, within the capacity of each law enforcer (whether as a judge, prosecutor, investigator, advocate, experts etc.) is encouraged to always ask the conscience about the deeper meaning of the law. What do the rules of procedure, principles, doctrines, etc. mean? Third, the law should be enforced within the capacity of each law enforcement officer.